0423 Chronic Insomnia And Altered Nocturnal Blood Pressure And Heart Rate Modulation. (27th April 2018) - Grimaldi, D; Carter, J R; Medali, L; Whitmore, H; Mokhlesi, B; Van Cauter, E
Abstract: Introduction: Increasing epidemiological evidence links insomnia to increased cardiovascular risk. In particular, an increased risk for developing hypertension has been reported in patients with chronic insomnia, although the mechanism remains unclear. In the present study we investigated the 24h profile of arterial blood pressure (BP) and heart rate (HR) in subjects with chronic insomnia to test the hypothesis that compared to healthy good sleepers, subjects with chronic insomnia exhibit an altered day-to-night BP and HR regulation. Methods: Ten subjects with chronic insomnia (42 ± 16 years, 24 ± 4 kg/m 2 ) and 8 healthy controls (34 ± 13 years, 26 ± 6 kg/m 2 ; p>0.05) without obstructive sleep apnea or any other sleep disorder underwent 24h beat-to-beat BP and HR recording (finger plethysmography) starting at 15:00h. During the study, subjects were instructed to maintain a semi-recumbent position while lying in bed except during sleep (23:00-7:00h). To evaluate the nocturnal decline of systolic and diastolic BP (SBP, DBP) and HR, daytime mean values (from 20:00 to 23:00h) and nighttime mean values (from 00:00 to 06:00h) were calculated and also expressed as % decline of nighttime values over daytime values. Results: Subjects with chronic insomnia had a blunted dipping of nocturnal BP compared to controls. The blunted dipping was more evident for DBP (DBP dipping: controls 11 ± 3%, insomnia: 5 ± 7%, p=0.032; SBP dipping: controls 11 ± 5%, insomniacs: 5 ± 8%, p=0.064). Higher HR values were observed during nighttime in subjects with chronic insomnia compared to controls (controls: 57 ± 7 bpm, insomniacs: 67 ± 7 bpm; p=0.025) associated with a blunted day-to-night HR decline (controls: 18 ± 6%, insomniacs: 11 ± 4%, p=0.042). Conclusion: Our findings suggest the presence of an altered nocturnal BP and HR modulation in subjects with chronic insomnia that can contribute to the increased cardiovascular risk Support (If Any): Merck: #13- 1214.